Law sought vs distracted walking - Sotelo, Yolanda (2017)
Councilor Maybelyn Rose Fernandez wants an "antidistracted walking ordinance" now that motorists have been barred from driving while using their mobile phones and other devices.
Keywords: Fernandez, Maybelyn Rose; anti-distracted walking ordinance; Dagupan City